Aldose Reductase Drives Hyperacetylation of Egr-1 in Hyperglycemia and Consequent Upregulation of Proinflammatory and Prothrombotic Signals - Vedantham, Srinivasan (American Diabetes Association, 2014)
Sustained increases in glucose flux via the aldose reductase (AR) pathway have been linked to diabetic vascular complications. Previous studies revealed that glucose flux via AR mediates endothelial dysfunction and leads to lesional hemorrhage in diabetic human AR (hAR) expressing mice in an apoE(−/−) background. Our studies revealed sustained activation of Egr-1 with subsequent induction of its downstream target genes tissue factor (TF) and vascular cell adhesion molecule-1 (VCAM-1) in diabetic apoE(−/−)hAR mice aortas and in high glucose–treated primary murine aortic endothelial cells expressing hAR. Furthermore, we observed that flux via AR impaired NAD(+) homeostasis and reduced activity of NAD(+)-dependent deacetylase Sirt-1 leading to acetylation and prolonged expression of Egr-1 in hyperglycemic conditions. In conclusion, our data demonstrate a novel mechanism by which glucose flux via AR triggers activation, acetylation, and prolonged expression of Egr-1 leading to proinflammatory and prothrombotic responses in diabetic atherosclerosis.